Sinergi jigsaw dan open educational resources (OER) dalam pembelajaran matematika: dampaknya terhadap komunikasi dan hasil belajar siswa - Bungel, Moh. Fikri; Wahyuningrum, Endang; Susandi, Ardi Dwi (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to assess the efficacy of an Open Educational Resources (OER)-based Jigsaw learning model on the mathematical communication skills and academic achievement of junior high school students.Design/methodology/approach: This quasi-experimental research employed a randomized pretest-posttest control group design involving seventh-grade students at SMPN 1 Balantak. Data were collected via multiple-choice tests for learning outcomes and descriptive tests for mathematical communication, subsequently analyzed using independent samples t-tests.Findings: The t-test results indicated significance values for learning outcomes (0.112) and communication skills (0.134) exceeding the 0.05 threshold. Consequently, the OER-based Jigsaw model did not yield a statistically significant effect compared to the expository model, despite the experimental group recording higher mean scores.Practical implications: These findings suggest that while the OER-based Jigsaw model serves as a viable instructional alternative, its implementation requires optimization to demonstrate a significantly superior impact compared to conventional methods.Originality/value: This research contributes insights regarding the integration of OER into the Jigsaw cooperative learning framework, specifically within the context of regional mathematics education.   Purpose: Penelitian ini bertujuan menguji pengaruh model pembelajaran Jigsaw berbasis Open Educational Resources (OER) terhadap kemampuan komunikasi matematis dan hasil belajar siswa SMP.Design/methodology/approach: Studi kuasi eksperimen ini menerapkan randomized pretest-posttest control group design pada siswa kelas VII SMPN 1 Balantak. Data dikumpulkan melalui tes pilihan ganda (hasil belajar) dan uraian (komunikasi), lalu dianalisis menggunakan independent sample t-test.Findings: Hasil uji-t menunjukkan signifikansi hasil belajar (0,112) dan komunikasi (0,134) > 0,05. Artinya, model Jigsaw-OER tidak berpengaruh signifikan dibandingkan ekspositori, meskipun rata-rata skor kelas eksperimen tercatat lebih tinggi.Practical implications: Temuan ini mengimplikasikan bahwa Jigsaw berbasis OER dapat diterapkan sebagai variasi strategi pembelajaran, namun pelaksanaannya memerlukan optimalisasi agar dampaknya lebih signifikan dibanding metode konvensional. Originality/value: Penelitian ini menawarkan wawasan mengenai integrasi sumber belajar terbuka (OER) ke dalam sintaks pembelajaran kooperatif Jigsaw dalam konteks pendidikan matematika di daerah.